DIGLOSIA AND THE PRESERVATION OF THE BALINESE LANGUAGE AMIDST THE DOMINANCE OF ENGLISH IN THE TOURISM SECTOR - NI Ketut Veri Kusumaningrum; Elsita Lisnawati Guntar; Ni Nyoman Widiani (Lingua Scientia, 2026)
This study examines the phenomenon of diglossia and the efforts to maintain the Balinese language in the context of the rapidly growing tourism sector in Bali. The dominance of English as the primary language of international tourism communication has created a complex sociolinguistic dynamic, shifting the functional role of the Balinese language in public and commercial spaces. This research employs a qualitative ethnographic approach, involving in-depth interviews with 30 informants consisting of tourism workers, indigenous community members, and local government officials in the Ubud, Kuta, and Sanur tourism areas. Data collection was conducted from June to December 2025. The findings reveal three main patterns: (1) a clear functional separation between Balinese as the H (High) variety and English as the superimposed H variety in tourism communication; (2) the emergence of code-switching and code-mixing as adaptive linguistic strategies; and (3) a significant weakening of intergenerational Balinese language transmission among the younger generation engaged in the tourism sector. Nevertheless, cultural and religious institutions such as the banjar and traditional ceremonies remain as resilient domains for Balinese language maintenance. This study recommends the integration of Balinese language and culture into tourism management policies as a sustainable language preservation strategy.